Differentiation of ripe and unripe fruit flour using mineral composition data—Statistical assessment - Abbas F.M. Alkarkhi; Wasin A.A. Alqaraghuli; N.R. Mohamed Zam; D.M.A. Manan; M.N. Mahmud; Nurul Huda (2020)
Data on the mineral composition and content of one heavy metal measured in three different fruit flours prepared from ripe and unripe fruits (pulp and peel) are presented. The mineral composition (sodium (Na), potassium (K), magnesium (Mg), calcium (Ca), zinc (Zn), copper (Cu), iron (Fe) and manganese (Mn)) and content of one heavy metal (lead (Pb)) of the flours were analyzed by atomic absorption spectrophotometry. The analysis showed that the data can be used for differentiation between different fruits and stages of ripeness, as revealed by discriminant analysis and cluster analysis. The data provided can be used by researchers and scientists in the differentiation of fruits based on major and minor mineral elements.